Constructing the Shape of the ‘Holy’: The Umayyad Conception of al-Masjid al-Aqṣā’s Identity - al-Ratrout, Haithem F.; Qamhieh, Khaled F.; El-Awaisi, Khalid (Journal of Al-Tamaddun, 2023)
The al-Aqsa Mosque, the holiest site of the Holy Land, underwent a major architectural transformation initiated by the Muslim Umayyad Caliph ‘Abd al-Malik ibn Marwān (r. 66-86 AH/ 685-705 CE). Through his comprehensive construction program, ‘Abd al-Malik established the architectural importance of the Sacred Rock and elevated it as one of the fundamental Islamic religious foci. The vision behind the mosque’s design is filled with religious enthusiasm and serves as a powerful architectural manifestation of ‘Abd al-Malik’s political manifesto rooted in religious expression. This study provides an analysis of the process of creating the general shape of the ‘Holy’ within the sacred architecture of the al-Aqsa Mosque and its reflection in the general image of Bayt al-Maqdis’ skyline. The research employs an interdisciplinary approach, re-examining and re-evaluating the historical literature and connecting it to archaeological observations and architectural coordination relevant to the subject of the study. The findings of this research shed light on the design concept of the al-Aqsa Mosque and make a significant contribution to clarifying our understanding of the early Islamic architecture of the site.